Synthesis, characterization and applications of low temperature melting glasses belonging to P2O5CaONa2O system. Issue 9 (15th June 2019) - Liu, W.; Sanz, J.; Pecharromán, C.; Sobrados, I.; Lopez-Esteban, S.; Torrecillas, R.; Wang, De-Yi; Moya, J.S.; Cabal, B.
Abstract: This study details the relationship between the structure, chemical composition and thermal properties of a series of calcium sodium phosphate glasses belonging to x P2 O5 - y CaO-(100− x − y )Na2 O system, which have been prepared by melt-quenching method. The glass compositions were limited by fixing the P2 O5 content ( x ) to 40, 45, 50, 55 and 60 mol%, and varying the CaO mol% ( y ) at 10, 15, 20, 25, 30 mol%. Glass transition (Tg ) and melting temperatures (Tm ) show a clear relationship with composition. The polymerization of the glass structure increases the higher the content of P2 O5 leading to an increase in Tg and Tm temperatures. Higher contents of calcium improve the phosphate network strength increasing Tg and Tm temperatures. Sodium ions, displaying lower charge-to-size ratio than calcium ions, decrease the phosphorous condensation reducing the Tg and Tm temperatures of glasses. The results obtained in this investigation show the feasibility to develop extremely low melting calcium sodium phosphate glasses with P2 O5 content of 45 mol%. Those results laid the foundation of employing these calcium sodium phosphate glasses as amorphous low melting temperature materials for further applications involving: a) melting temperature adjustment, such as fire-retardant additive in polymer composites; b) nanoparticle binder, due to its low melting temperature, nanoparticles can be safely embedded into this glass avoiding thermal coalescence. Examples of such applications are described in this work.